American hangman: a biography of Amos Lunt, the executioner of San Quentin - Buhk, Tobin T. (McFarland & Company, Inc., 2022)
"In the 1890s, Amos Lunt served as the San Quentin hangman, tying the nooses that brought the most dangerous criminals in the Wild West to their deaths. A former police chief who became the hangman of San Quentin due to an unfortunate turn of events, Lunt stood on the gallows alongside bank robbers, desperadoes and assassins throughout a five-year career. This book follows Lunt's trail from the Santa Cruz police department to the San Quentin State Prison. Covering his interesting friendship with a series of death row inmates to the gradual deterioration of his sanity, it is a one-of-a-kind biography that profiles an American executioner. Also profiled are his subjects--twenty of the West's most heinous criminals--as well as Lunt's preparations for their hangings and their final moments on the gallows"--